Digital Laser-Sintered Expander in Adolescent Patient with Hyperdontia and Molar Impaction - Greta Roussanova Yordanova-Kostova; Emanuel Emiliyanov; Nikolay Yanev (Case Reports in Dentistry)
Supernumerary teeth can have normal or abnormal morphologic structure and characteristics, and their impacted form is diagnosed usually during X-ray examinations. In this case report, the presented patient is a 16-year-old female with anterior and right posterior open bite and bilateral posterior crossbite, upper right supernumerary paramolar, and impacted second and third molars. The paramolar development was the reason for the asymmetric growth of the alveolar bone in the upper jaw. The development of the bone is connected with the development of the teeth, and one additional tooth leads to extensive development in the maxilla. There is a risk of gingival recession occurrence when leveling the lower incisors due to the thin gingival biotype. A combined surgical-orthodontic treatment was done according to the following plan: extraction of supernumerary paramolar, germectomy of the upper right third molar (18) and at the same time periodontal graft in the lower anterior segment. A digitally three-dimensional (3D) printed appliance for rapid maxillary expansion was used for the transverse insufficiency of the upper jaw. The upper dental arch expander was designed with distal extension in the area of the upper right second molar (17). The extension was used as an anchorage during the orthodontic traction of the second molar. The treatment continued with a fixed orthodontic appliance—braces in the upper and lower jaw. With the extraction of the impacted and supernumerary teeth in the right maxillary segment, the eruption of 17 was stimulated and a change in the height of the alveolar bone was achieved. This favored the vertical changes and normalization of the occlusion. The maxillary expansion was also a significant factor in normalizing the occlusion. Observations on paramolar behavior showed that more often they develop in the bone and do not erupt. Each clinical case is highly individual, and patients seek orthodontic treatment at different stages of dentition development and corresponding development of the supernumerary teeth.